180 think-aloud math word problems - Nessel, Denise; Newbold, Ford. (New York : Scholastic, 2003)
Describes a "read-and-think" approach to understanding and solving math word problems for students in grades four through six, and features 180 three-part prolems in multiplication, division, time, money, fractions, and other math topics.
"A great way to prepare kids for standardized tests!"--Cover.
"Dozens of quick, daily exercises and strategies that give kids the tools they need to tackle and triumph over math word problems"--Cover.
"Grades 4-6"--Cover.
Includes bibliographical references (p. 11).
Professional
Keywords: Creative activities and seat work; Mathematics -- Study and teaching; Teaching -- Aids and devices; Word problems (Mathematics) -- Study and teaching; Creative activities; Mathematics -- Study and teaching; Teaching -- Aids and devices; Word problems (Mathematics) -- Study and teaching